Retrospective review of women diagnosed with premature ovarian insufficiency - Chirwa, Nyatozi (Department of Obstetrics and Gynaecology, 2019)
Premature ovarian insufficiency (POI) is a clinical syndrome defined by loss of ovarian activity before the age of 40. It is characterized by menstrual disturbance (amenorrhoea or oligo-(amenorrhoea), raised gonadotrophin concentrations and low oestradiol levels. The diagnosis is confirmed by detection of raised serum follicle stimulating hormone and low oestradiol levels. POI can occur spontaneously, but it may also result from genetic defects, chemotherapy, radiotherapy or surgery. Oestrogen deprivation as a result of POI has serious implications for female health. In particular, bone mineral density, cardiovascular health, neurological systems and sexual health, may be impacted. The challenge posed by this important condition is the absence of standardized diagnostic criteria and management guidelines within our clinical practice. There are no local data about the causes and prevalence of POI in South Africa or adherence to international recommendations for management. The aim of this study was to review the women who have presented to our gynaecological endocrine service with POI and to assess their diagnosis and presentation. Based on this information we plan to adjust, where necessary, our current protocol of investigations. Methods: The study was conducted at the Gynaecological Endocrine clinic, at Groote Schuur Hospital (GSH), South Africa over a period of 11 months (June 2016 to May 2017). It was a retrospective folder review of women diagnosed with POI from 1983 to date. Ethics approval was granted by the Human Research Ethics Committee of the Faculty of Health Sciences of UCT [HREC REF:315/2016] and further permission to access patient records was given by the Hospital committee. A total of 442 patients with the diagnosis of POI were identified using the card index system in our Gynaecological Endocrine Clinic. Clinical folders and microfilms were reviewed and information transferred to a template. The data were then entered using a Microsoft Excel spreadsheet and analysed. A total of 303 patients aged less than 40 presenting with primary or secondary amenorrhoea/oligo-menorrhoea of at least 6 months’ duration with serum FSH concentrations of >25mIU/mL on at least two occasions were evaluated. Comparison between groups was done using the t-test with a p-value of less than 0.05 being considered significant. Results A total of 369 patients with POI were identified in our clinic and we were able to review 303 of these clinical records (66 missing). Patients were aged 12-40 years at the initial visit. Serum levels of FSH, LH and oestradiol were similar in patients with primary and secondary amenorrhoea. Chromosomal abnormalities were more likely in the 38 patients with primary amenorrhoea (57.6%) than in those with secondary amenorrhoea (23.6%). Of 237 patients who presented with secondary amenorrhoea, more complained of symptoms of oestrogen deficiency (78.2%) and had been pregnant before diagnosis (53.2%) than those with primary amenorrhoea (p<0.001). Immune disturbances were present in 4.6% patients, mostly in women with secondary amenorrhoea. The most common karyotype in the 38 patients with primary amenorrhoea was 45X0 (n=18). Of the patients with primary amenorrhoea 4 had gonadal dysgenesis. After completing investigations, the cause was not identified in 36.3% (n=110) of the patients, followed by genetic causes 20.8% (n=63), chemo/RT 9.6% (n=29), iatrogenic 5.0% (n=15) and autoimmune causes 4.6% (n=14). Investigations were incomplete in 22.8% n=72) of the women due to failure to continue follow-up. Conclusion: It is important to offer a comprehensive assessment to women with POI to establish the cause and institute appropriate treatment. Counselling on long term management and fertility options is essential. Many women do not complete investigations after receiving the initial diagnosis and greater awareness of POI needs to be developed, along with increased education of women planning fertility later in life, particularly if they are at risk of POI. Women with POI have unique needs that require special attention and our clinical services need to address these.